2000
DOI: 10.1177/01461672002611009
|View full text |Cite
|
Sign up to set email alerts
|

Public Self-Focus and Sex Differences in Behavioral Self-Handicapping: Does Increasing Self-Threat Still Make it “Just a Man’s Game?”

Abstract: The pres ent study exam ined the effects of pub lic self-focus and par tic i pants

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
96
0
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(113 citation statements)
references
References 34 publications
10
96
0
7
Order By: Relevance
“…Based on past findings that women are more critical of individuals that withdraw effort and that women do not behaviorally handicap even when the evaluative threat of the performance is increased (Hirt et al, 2000), we proposed that gender differences in behavioral self-handicapping could be due to women placing more value on putting forth effort. Our goal in the present research was to develop and examine measures of effort beliefs that could be used to test this explanation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on past findings that women are more critical of individuals that withdraw effort and that women do not behaviorally handicap even when the evaluative threat of the performance is increased (Hirt et al, 2000), we proposed that gender differences in behavioral self-handicapping could be due to women placing more value on putting forth effort. Our goal in the present research was to develop and examine measures of effort beliefs that could be used to test this explanation.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supporting the role of effort beliefs in gender differences in self-handicapping Earlier work on the gender difference in behavioral self-handicapping largely focused on the idea that men experience more evaluative threat and thus have greater motivation to self-handicap. For example, based on the finding that self-handicapping is at least partly motivated by impression management concerns (Kolditz & Arkin, 1982), Hirt et al (2000) examined whether increasing the evaluative threat of a performance via public self-focus would increase behavioral self-handicapping among men and women. Although men responded to public self-focus with increased behavioral self-handicapping, women did not.…”
Section: Introductionmentioning
confidence: 99%
“…Hirt et al, 1991Hirt et al, , 2000. Participants were also told that the researchers were interested in examining the effect of practice on the exam, and so they were asking participants to either complete a set amount of practice problems or to not practice at all.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The two measures were highly correlated (r ϭ .91). Consistent with past work (see Hirt et al, 1991Hirt et al, , 2000, these measures were standardized and summed (␣ ϭ .95 [reversed], proud, competence, resourceful, capable) were also combined into a single measure (␣ ϭ .70). Initial analyses revealed no significant effects of gender, and so this variable was dropped from further consideration.…”
Section: Overviewmentioning
confidence: 99%
“…This is evidenced in the consistent observation that self-handicapping is especially likely to occur in response to non-contingent success feedback Arkin & Baumgartner, 1985;Mayerson & Rhodewalt, 1988;Hirt, Deppe, & Gordon, 1991). Research conducted by Hirt, McCrea, and Kimble (2000) has shown that this relationship is mediated by feelings of concern for failure.…”
Section: Uncertainty Choice and Controlmentioning
confidence: 94%